Agriculture calendar for the maize crop in Sinop, Mato Grosso State, Brazil - Rodrigo Garcia Garcia; Rivanildo Dallacort; Willian Krause; Edenir Maria Serigatto; Cleonir Andrade Faria Júnior (Pesquisa Agropecuária Tropical, 2013)
This study aimed at determining an agriculture calendar for the maize crop in Sinop, Mato Grosso State, Brazil, by evaluating rainfall, air temperature and evapotranspiration. Based on the thermal requirements of the maize hybrid, the heat unit accumulation or degree-day methods were used to determine the occurrence of phenological stages, considering the highest (30ºC) and lowest (10ºC) temperatures. The growing season was determined by analyzing the variation of the total 10-days average rainfall and evapotranspiration for that locality. The calendar was established according to the thermal requirements to complete the phenological stages, rainfall distribution during these stages and probability of occurring at least five dry days per 10-days period. The best sowing time took place between the 30th and 32nd 10-days period, at the end of October and beginning of November.